Ictal deafness in drug‐resistant MRI‐negative epilepsy. Issue 2 (30th April 2019) - Ikegaya, Naoki; Nakagawa, Eiji; Sugai, Kenji; Sasaki, Masayuki; Saito, Takashi; Sumitomo, Noriko; Iijima, Keiya; Kimura, Yuiko; Kaneko, Yuu; Iwasaki, Masaki
ABSTRACT: Ictal clinical semiology indicates where the patient's seizure arises from and how it progresses. A patient's description of a focal sensory seizure may support a surgical decision even when MRI and PET abnormalities are absent. Ictal deafness is a focal auditory seizure characterized by suppression of hearing, presumably originating from the auditory cortex in the temporal lobe. However, the precise localization has not been confirmed with surgical cases. We present a case in which the region from where ictal deafness arose was confirmed by intracranial electroencephalography, with successful epilepsy surgery and review other published cases.